Developing a reliable and valid patient measure of safety in hospitals (PMOS): a validation study. Issue 7 (24th December 2013) - McEachan, Rosemary R C; Lawton, Rebecca J; O'Hara, Jane K; Armitage, Gerry; Giles, Sally; Parveen, Sahdia; Watt, Ian S; Wright, John; ,
Abstract : Introduction: Patients represent an important and as yet untapped source of information about the factors that contribute to the safety of their care. The aim of the current study is to test the reliability and validity of the Patient Measure of Safety (PMOS), a brief patient-completed questionnaire that allows hospitals to proactively identify areas of safety concern and vulnerability, and to intervene before incidents occur. Methods: 297 patients from 11 hospital wards completed the PMOS questionnaire during their stay; 25 completed a second 1 week later. The Agency for Healthcare Research and Quality (AHRQ) safety culture survey was completed by 190 staff on 10 of these wards. Factor structure, internal reliability, test-retest reliability, discriminant validity and convergent validity were assessed. Results: Factor analyses revealed 8 key domains of safety (eg, communication and team work, access to resources, staff roles and responsibilities) explaining 58% variance of the original questionnaire. Cronbach's α (range 0.66–0.89) and test-retest reliability (r=0.75) were good. The PMOS positive index significantly correlated with staff reported 'perceptions of patient safety' (r=0.79) and 'patient safety grade' (r=−0.81) outcomes from the AHRQ (demonstrating convergent validity). A multivariate analysis of variance (MAMOVA) revealed that three PMOS factors and one retained single item discriminated significantly across the 11 wards. Discussion: The PMOS is the first patient questionnaire used to assess factors contributing to safety in hospital settings from a patient perspective. It has demonstrated acceptable reliability and validity. Such information is useful to help hospitals/units proactively improve the safety of their care.